An Evidence-Based Approach to the Treatment of Acute Whiplash Injury - Les Barnsley (Pain Research and Management)
This review has two components. The first is a selective, narrative background of some of the issues surrounding acute whiplash. The latter part is a more systematic review of the available evidence concerning the management of acute whiplash as it stood in March 2001.